Cross-talk of m6A methylation modification and the tumor microenvironment composition in esophageal cancer - Song, Pan; Ye, Jinmao; Zhang, Haiyang; Li, Yishu; Cao, Ruizhi; Feng, Yang; Zhang, Lei; Sun, Min (Frontiers in Immunology, 2025)
BackgroundEsophageal cancer (EC) remains a significant clinical challenge, characterized by its aggressive nature and poor prognosis. Current therapeutic strategies, including targeted therapies, have limitations due to the complex interplay between tumor heterogeneity and the tumor microenvironment (TME). However, the specific contributions of N6-methyladenosine (m6A) methylation to the TME in EC are yet to be fully elucidated.MethodsThrough comprehensive bioinformatics analyses, a detailed examination of m6A regulators were conducted in EC using datasets from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO). Single-cell RNA sequencing (scRNA-seq) and a consensus clustering algorithm was employed to classify m6A modification patterns and analyze their relationships with immune cell infiltration and clinical outcomes. Additionally, an m6A scoring system was developed based on principal component analysis to assess the prognostic value of identified m6A modification patterns.ResultsThe findings revealed two distinct m6A modification clusters associated with divergent TME characteristics and immune infiltration profiles. Patients exhibiting the immune-inflamed phenotype (m6A cluster B) demonstrated significantly improved survival compared to those with the immune-excluded phenotype (m6A cluster A). Notably, m6A scores correlated positively with immune cell presence and related with adverse prognostic outcomes, indicating their potential as predictive biomarkers for immunotherapy responses. A low m6A score indicated a better response to immunotherapy.ConclusionThis study highlights the critical role of m6A methylation in shaping the TME and influencing immune dynamics in EC. The m6A score developed herein provides a novel quantitative tool for predicting tumor behavior and treatment efficacy, paving the way for more personalized immunotherapeutic strategies in clinical practice. This scoring system illustrates a strong correlation of EC with TME immune cell composition, suggesting potential as a biomarker for targeted therapeutic strategies for EC.